PENGARUH MENONTON FILM UPIN DAN IPIN TERHADAP KARAKTER SISWA - Sudarto Sudarto; Achmad Shabir; Achmad Hidayat Nasrum (Sekolah Tinggi Pariwisata Mataram, 2023)
This research is a causal correlation research that aims to determine whether there is or there is not an effect of watching Upin and Ipin films to the character of students at SDN 100 Simpursia, Pammana District, Wajo Regency. The population in this study were all students at SDN 100 Simpursia and the sample used was a total of 77 engineerung students. The data collection used was a questionnare. The data analysis technique used was descriptive analysis and inferential analysis. The results obtained in this research were that there was an effect of watching the animas film upin dan ipin test on the character of SDN 100 Simpursia, Pammana District, Wajo Regency with a significance value of 0,000 smaller and probability 0,05. Which means tha H0 is reject and Ha is accepted, which means that there is an effect of watching upin and ipin animated films to student characters. This proves that watching the animated films upin and ipin contributes as much 25,9% to the self character, while the rest is influenced by other factors of the research